Dosimetry evaluation of photon beam profile characteristics for different treatment parameters of quality assurance - Taghreed Ahmed Nghaimesh; Siham Sabah Abdullah; Hadeel Kamil Abdullah; Abdulrahman Mohammed Abdulbaqi (Journal of the Pakistan Medical Association)
Objective: To compare beam profiles of MatriXX scanning system and water phantom for different treatment parameters.